2011
DOI: 10.1002/jssc.201000690
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and chromatographic performance of calix[4]crown‐5 macrocycle‐bonded silica stationary phase

Abstract: A new calix[4]crown-5 macrocycle-bonded silica stationary phase (CL-CIMS) was prepared and applied at the same time to develop a chromatographic procedure to separate aromatic amines, phenols and drugs in this study. The chromatographic behaviors of the prepared stationary phase for these analytes were studied and compared with those of ODS (octadecylsilane). The effect of organic modifier content and pH of the mobile phase on retention and selectivity of these compounds were investigated. Some aromatic amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Immobilized calix[4]arene ionophores 10 and 11 were characterized by elemental analysis, UV spectra, and FTIR. Bounded amount of calixaren precursors 5 and 6 onto polymeric backbone was calculated according to literature procedure (mmol/g) = %C × 10/12 n , where %C is the mass percentage of carbon in the product and n is the number of carbon in the ligand and found to be approximately 0.30 mmol of 5 /g of polymer and 0.22 mmol of 6 /g of polymer 28. Furthermore, to support the obtained elemental analysis data for immobilized calix[4]arene ionophores 10 and 11 , the amount of remaining unreacted calixarene precursors 5 and 6 after immobilization reaction was also analyzed spectrophotometrically at 284 nm and calculated from the initial and final absorbance values of the compounds 5 and 6 before and after the immobilization reaction, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilized calix[4]arene ionophores 10 and 11 were characterized by elemental analysis, UV spectra, and FTIR. Bounded amount of calixaren precursors 5 and 6 onto polymeric backbone was calculated according to literature procedure (mmol/g) = %C × 10/12 n , where %C is the mass percentage of carbon in the product and n is the number of carbon in the ligand and found to be approximately 0.30 mmol of 5 /g of polymer and 0.22 mmol of 6 /g of polymer 28. Furthermore, to support the obtained elemental analysis data for immobilized calix[4]arene ionophores 10 and 11 , the amount of remaining unreacted calixarene precursors 5 and 6 after immobilization reaction was also analyzed spectrophotometrically at 284 nm and calculated from the initial and final absorbance values of the compounds 5 and 6 before and after the immobilization reaction, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was shaken vigorously in a stoppered glass tube with a mechanical shaker for 2 min, and then magnetically stirred in a thermostated water bath at 25°C for 1 h, and finally left standing for an additional 30 min. Then, the concentration of dichromate or phosphate ion remaining in the aqueous phase was determined spectrophotometrically as described previously 22, 28. Blank experiments showed that no dichromate or phosphate extraction occurred in the absence of the receptors 5–7 and 9 , immobilized receptors 10 and 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Silica gel (particle size 5 lm, pore size 100 A°and a specific surface area 300-400 m 2 /g) was treated with 3-(aminopropyl)-trimethoxysilane in toluene, and under nitrogen atmosphere to yield aminopropyl functionalized silica particles (APS) which was characterized by elemental and thermal analysis [23].…”
Section: Resultsmentioning
confidence: 99%
“…16 Yin et al reported p-tert-butylcalix [8]arene-bonded silica monoliths for the separation of regioisomers, 22 Erdemir and Yilmaz prepared the calix [4]crown-5 macrocycle-bonded silica stationary phase and a new 1,3alternate-calix [4]arene-bonded HPLC stationary phase to analyze their usability for the separation of aromatic amines and drugs. 23,24 Hu et al reported a new 25,27-bis-[2-(5-methylthiadiazole)thioethoxyl]-26,28-dihydroxy-para-tert-butyl calix [4]arene stationary phase for the separation of aromatic amines and anilines. 25 These results conrm the usability of reversephase packing with inclusion capability of calixarene-bonded stationary phases.…”
Section: Introductionmentioning
confidence: 99%